2020
DOI: 10.1111/ajt.15595
|View full text |Cite
|
Sign up to set email alerts
|

Donor-specific antibodies detected by single antigen beads alone can help risk stratify patients undergoing retransplantation across a repeat HLA mismatch

Abstract: Whether reexposure to mismatched HLA antigens (RMM) in the setting of a negative crossmatch is associated with increased immunological risk remains an area of uncertainty. This is due to evidence derived predominantly from registry data, which lacks comprehensive information on alloantibody and rejection. In this study, we analyze the impact of low‐level preformed donor‐specific antibodies (DSA) against an RMM on transplant outcomes. From 1988 consecutive renal transplant recipients, we analyzed 179 patients u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
10
1
Order By: Relevance
“…Recent studies have shown that the risk of antibody-mediated rejection and premature graft loss is associated with preformed DSA and not with the level of sensitization, measure by cPRA, as previously suggested [ 19 ]. Also, recent data suggest that, in the absence of detectable preformed DSA, reexposure to mismatched HLA antigens present in the first kidney transplant is not associated with de novo DSA development, rejection, or allograft loss [ 5 ]. Finally, the proportion of patients with previous allograft nephrectomy, which has been associated with an increased risk of development of anti-HLA antibodies [ 20 ], was comparable between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that the risk of antibody-mediated rejection and premature graft loss is associated with preformed DSA and not with the level of sensitization, measure by cPRA, as previously suggested [ 19 ]. Also, recent data suggest that, in the absence of detectable preformed DSA, reexposure to mismatched HLA antigens present in the first kidney transplant is not associated with de novo DSA development, rejection, or allograft loss [ 5 ]. Finally, the proportion of patients with previous allograft nephrectomy, which has been associated with an increased risk of development of anti-HLA antibodies [ 20 ], was comparable between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous limitations in our study. There are no data regarding the outcomes of previous first and second transplants, including the dose of rATG, the incidence of DGF, level of renal function, survival [ 2 ], and reexposure to HLA mismatched antigens [ 5 ], all associated with clinical outcomes after retransplantation [ 2 ]. We also do not have data on HLA C, DP and DQ mismatches nor the presence of DSA against these antigens, which are becoming more relevant for both short and long-term graft survivals [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason for a continuously better graft survival of repeat transplantation is the development of better techniques of HLA class II typing as well as HLA-antibody detection [ 27 – 32 ]. Complement-dependent crossmatch had for a long time been the only method to prevent hyperacute rejection and to test for HLA antibodies [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lucisano et al analyzed a single-center cohort for the impact of preformed donor-specific antibodies against repeated mismatches on transplant outcomes. 154 Despite negative cross-matches, patients with low-level preformed antibodies against repeated HLA mismatches were at risk of antibody-mediated rejection and death-censored graft loss. In contrast, without the preformed antibody, a repeated mismatch was not associated with de novo donor-specific antibody development, rejection, or allograft loss.…”
Section: Repeated Hla Mismatchesmentioning
confidence: 99%